CHINA RISE SYNDROMES? DRAFTING NATIONAL SCHOOLS OF INTERNATIONAL RELATIONS IN ASIA - Chih-Yu Shih (Сравнительная политика, 2015)
The rise of China is now one of the primary issues in IR literature. However, this development promotes also changes in the structure of the discipline itself, as it fosters self-reflection in the rapid expansion of the Chinese IR school. Moreover, the quest for Chinese theory of IR provokes other Asian countries to conceptualize their place in the world, in order not to be intellectually submerged by the rising neighbour. This theorizing is enlightened by the national traditions of thinking about international politics, largely overseen in the West. This trend promotes genuine liberalization of the discipline.